Managing the risk of bacterial meningitis among healthcare workers. (29th November 2018) - Ferraro, M; Morucci, L; Coppeta, L; De Carolis, G; Pietroiusti, A; Franco, E; Magrini, A
Abstract: Background: Meningococcal disease is generally caused by A, B, C, W and Y subgroups of Neisseria meningitidis . In 2015, the Italian mass media focused on this disease due to the death of two nurses. This generated alarm in the general population, especially in healthcare workers (HCWs). The Occupational Medicine department of the Foundation PTV Polyclinic Tor Vergata (PTV) offered free MenACWY vaccine to HCWs and to students of the University of Rome Tor Vergata. Aims: To analyse the prevalence of N. meningitidis in PTV, a large teaching hospital, and to evaluate preventive measures offered to individuals at risk (i.e. HCWs and students). Methods: The Hospital Informatic Service provided data about patients admitted to PTV from January 2012 to December 2016. Hospital Discharge Registers were analysed and all cases of meningitis were selected. MenACWY vaccine administered to HCWs and students of PTV in 2017 was analysed. Results: There was just one case of meningococcal disease in 2016. Of the 117 MenACWY vaccines administered, 42% were given to students, 32% to doctors, 8% to nurses, 2% to clerks and 16% to other healthcare professionals. Conclusions: International guidelines recommend MenACWY vaccine for microbiologists exposed to N. meningitidis isolates. The Italian Legislative Decree 81/2008, however, states that occupational physicians can adopt special protective measures such as vaccination programmes for HCWs. The response rate highlights how perceived risk may influence behaviour even in populations with a higher background knowledge than the general population.